ANALYSIS OF CSR IMPLEMENTATION AND CURRENT RATIO ON STOCK PRICES OF CONVENTIONAL BANKING LISTED ON IDX 2016-2020 - Pradani, Devi Dias; Widiasmara, Anny (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
There are several ways that can be used by investors in determining whether or not a company is good. Such as looking at the way in which CSR has been implemented by the company or looking at the company's annual financial statements. According to Untung (2009:1):